The Mediating Role of Entrepreneurial Self-Efficacy and Attitude in Determinants of Green Entrepreneurship Intention - Anisa Okta Viana; Amir Mahmud; Lyna Latifah (Universitas Negeri Semarang, 2025)
This study examines the role of entrepreneurial self-efficacy and attitude in mediating the relationship between teacher support, teaching factory, industrial work practices, and green entrepreneurship intentions. This type of research uses quantitative research with causality research. The population of this study was 393 grade XII students majoring in Online Business and Marketing at SMK throughout Semarang City. The sample in this study was 190 students with a proportionate stratified random sampling. The data were processed using primary data from questionnaires distributed to grade XII students majoring in Online Business and Marketing at 7 SMK in Semarang City. The data analysis method used was descriptive analysis and Structural Equation Model (SEM) with SmartPLS 4.0. The results showed that the research model had met the validity and reliability of the construct. The results indicate that teacher support and entrepreneurial attitudes have a direct effect on green entrepreneurship intentions. Teaching factories, industrial work practices, and entrepreneurial self-efficacy do not have a direct effect on green entrepreneurial intention. Entrepreneurial self-efficacy cannot mediate the determinants of green entrepreneurial intention. Further research can be developed by adding variables related to measuring the level of environmental awareness of students